AmICog – mobile technologies to assist people with cognitive disabilities in the work place - Gómez, Javier; Alamán, Xavier; Montoro, Germán; Torrado, Juan C.; Plaza, Adalberto (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2014)
This paper presents the system AmICog, designed specifically to assist people with cognitive disabilities in their workplaces. To do that we employ mobile devices for two different purposes: on the one hand, to show interactive guides adapted to the user, the task and the user’s context. On the other hand, to locate and provide directions in indoors environments.